2014
DOI: 10.1016/j.biocel.2014.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Linsitinib (OSI-906) antagonizes ATP-binding cassette subfamily G member 2 and subfamily C member 10-mediated drug resistance

Abstract: In this study we investigated the effect of linsitinib on the reversal of multidrug resistance (MDR) mediated by the overexpression of the ATP-binding cassette (ABC) subfamily members ABCB1, ABCG2, ABCC1 and ABCC10. Our results indicate for the first time that linsitinib significantly potentiate the effect of anti-neoplastic drugs mitoxantrone (MX) and SN-38 in ABCG2-overexpressing cells; paclitaxel, docetaxel and vinblastine in ABCC10-overexpressing cells. Linsitinib moderately enhanced the cytotoxicity of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Our results indicated that voruciclib stimulated the ATPase activity of both ABCB1 and ABCG2, suggesting that it interacts with the drug-substrate-binding site and might competitively inhibit ABCB1 and ABCG2 activity [41-43]. Lastly, investigation of cell death revealed that voruciclib, at non-toxic concentration of 5 µM, potentiated paclitaxel or mitoxantrone-mediated apoptosis in drug resistant SW620/AD300 or NCI-H460/MX20 cells.…”
Section: Discussionmentioning
confidence: 95%
“…Our results indicated that voruciclib stimulated the ATPase activity of both ABCB1 and ABCG2, suggesting that it interacts with the drug-substrate-binding site and might competitively inhibit ABCB1 and ABCG2 activity [41-43]. Lastly, investigation of cell death revealed that voruciclib, at non-toxic concentration of 5 µM, potentiated paclitaxel or mitoxantrone-mediated apoptosis in drug resistant SW620/AD300 or NCI-H460/MX20 cells.…”
Section: Discussionmentioning
confidence: 95%
“…The sensitivity of cells to anticancer drugs was measured as previously described [32] using the MTT colorimetric assay.…”
Section: Methodsmentioning
confidence: 99%
“…Their substrate spectrum is considerably overlapping and includes many steroid-like compounds. Beclomethasone dipropionate (200), mometasone furoate (201), and ciclesonide (202, Fig. 30) inhibit the efflux activity in a dose-dependent manner at 0.1 to 10 μM.…”
Section: Hormonesmentioning
confidence: 97%